City Analytics : Competitive Cities for Jobs and Growth, Companion Paper 1 - Fikri, Kenan; Zhu, T. Juni (World Bank, Washington, DC, 2016)
interest in studying city competitiveness has skyrocketed in the past few years, although the topic itself is far from new. Mayors and city leaders have long worried about the obstacles to job creation, competitiveness, and economic growth that plague their cities. The objective of this paper is to present key findings from the quantitative analysis of the drivers of competitiveness in cites around the world.